2016
DOI: 10.2147/ott.s103640
|View full text |Cite
|
Sign up to set email alerts
|

Decreased expression of SLC39A14 is associated with tumor aggressiveness and biochemical recurrence of human prostate cancer

Abstract: ObjectiveSolute carrier family 39, member 14 (SLC39A14), has been identified as a potential biomarker for various cancers. However, its roles in prostate cancer (PCa) are still unclear. The aim of this study was to investigate the clinical significance of SLC39A14 in patients with PCa and its functions in malignant phenotypes of PCa cells.Patients and methodsSubcellular localization and expression pattern of SLC39A14 protein were examined by immunohistochemistry. Then, the associations of SLC39A14 expression w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…In fact, a comparison of healthy and cancerous cell lines suggested that SLC proteins have greater changes in their coexpression networks than protein kinases [28]. Proteins like SLC2A1, SLC39A14, and SLC16A1 may serve as prognostic biomarkers in cancers due to their central role in the development of cancer and responses to treatments [551][552][553]. Thus, it is imperative to continue studying transport proteins in a comprehensive manner, focusing not only on individual transport functions, but also unraveling the complex relationships between different transporters and metabolic states.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, a comparison of healthy and cancerous cell lines suggested that SLC proteins have greater changes in their coexpression networks than protein kinases [28]. Proteins like SLC2A1, SLC39A14, and SLC16A1 may serve as prognostic biomarkers in cancers due to their central role in the development of cancer and responses to treatments [551][552][553]. Thus, it is imperative to continue studying transport proteins in a comprehensive manner, focusing not only on individual transport functions, but also unraveling the complex relationships between different transporters and metabolic states.…”
Section: Discussionmentioning
confidence: 99%
“…ZIP14 is localized to the plasma membrane and endosome, and expressed in the small intestine, liver, pancreas, and heart [ 85 , 86 ]. Recent studies have shown that ZIP14 is highly expressed in the various cancers in human including the colorectal cancer, hepatocellular cancer, and prostate cancer [ 87 , 88 , 89 , 90 ]. In Zip14 -KO mice with dwarf body sizes, osteopenia, and impaired skeletal growth, cellular and molecular investigations revealed that ZIP14 modulates G protein-coupled receptor-mediated cAMP-CREB signaling by suppressing basal phosphodiesterase (PDE) activity ( Figure 4 D) [ 38 ].…”
Section: Overview Of Mammalian Zrt- and Irt-like Protein (Zip) Tramentioning
confidence: 99%
“…Researchers have revealed that the aforementioned five methylation sites may be crucial in cancer development. SLC39A14 has been identified as an independent factor for predicting the biochemical recurrence-free survival of patients with prostate cancer, and the decreased expression of SLC39A14 is associated with the tumor aggressiveness of human prostate cancer [ 32 ]. PREX2 (also known as P-Rex2 ) was highly expressed in the brain, heart, skeletal muscle, placenta, and lymph node and promoted cancer cell migration and/or invasion [ 33 35 ].…”
Section: Discussionmentioning
confidence: 99%